Biomass-Derived Functional Silica Materials for Hydrogen Storage: A Short Review - Mohammed Faraj Saeid; Bashir Abubakar Abdulkadir; Herma Dina Setiabudi (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
Hydrogen storage remains one of the foremost challenges in the transition to a clean energy economy. While extensive research has focused on metal hydrides, carbon materials, and complex sorbents, biomass-derived silica materials with high purity (90 wt.%), large surface areas (297-895 m2.g-1), and mesopores (3-60 nm) show strong potential for hydrogen storage but remain largely unexplored. This review highlights the synthesis, structural properties, and hydrogen storage potential of biomass-derived functional silica materials, with a particular focus on rice husk (RH) and bamboo as a sustainable and abundant precursor. Two principal silicon extraction strategies, combustion and alkali treatment, are discussed, emphasizing their influence on silica purity, morphology, and amorphous structure retention. Thermochemical processes, including acid leaching and controlled calcination, are shown to be essential for removing impurities and tailoring textural properties such as surface area, pore volume, and pore architecture. RH-derived silica supports exhibit outstanding effectiveness in dispersing transition metals like Ni and Fe, which in turn significantly improve hydrogen sorption kinetics, catalytic efficiency, and the long-term stability of the material. Additionally, the review explores how various synthesis pathways are expected to influence the performance of resulting materials in hydrogen storage systems, noting how structural collapse during reprecipitation or thermal treatment can negate surface advantages if not properly managed. The combined advantages of sustainability, tunable structural properties, and seamless compatibility with existing hydrogen storage strategies position biomass-derived silica as a highly promising next-generation platform for advanced hydrogen storage applications. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).